2023
DOI: 10.3390/heritage6020111
|View full text |Cite
|
Sign up to set email alerts
|

Post-Medieval Wrecks in the Western Mediterranean and Pottery: The Mortella II Wreck (1527) and the Chronology of Montelupo Tin-Glazed Earthenware

Abstract: This paper discusses and underlines the importance of investigations on post-medieval shipwrecks, particularly for wrecks where archival documentation is also available, in relation to gaining a better knowledge of tin-glazed tableware produced in Montelupo (Florence, Tuscany). The case of the Mortella II wrecks is interesting in this sense and also shows how an exact dating of the wreck can allow for a revision of the chronologies of the ceramic classes found on board. In the case of the majolica of Montelupo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…"The Mortella II Wreck, a Genoese Merchantman Sunk in 1527 in Corsica (Saint-Florent, France): A Preliminary Assessment of the Site, Hull Structures and Artefacts" [5] is the full study of the two wrecks of "La Mortella II and III" located in Corsica. The study is completed by the article "Post-Medieval Wrecks in the Western Mediterranean and Pottery: The Mortella II Wreck (1527) and the Chronology of Montelupo Tin-Glazed Earthenware" [6], which includes a preliminary study of the ceramics found in the 2021 excavation that was conducted in the area of the wreck of the Mortella II. The material found is of high interest for determining the chronology of the wreck (1527).…”
mentioning
confidence: 99%
“…"The Mortella II Wreck, a Genoese Merchantman Sunk in 1527 in Corsica (Saint-Florent, France): A Preliminary Assessment of the Site, Hull Structures and Artefacts" [5] is the full study of the two wrecks of "La Mortella II and III" located in Corsica. The study is completed by the article "Post-Medieval Wrecks in the Western Mediterranean and Pottery: The Mortella II Wreck (1527) and the Chronology of Montelupo Tin-Glazed Earthenware" [6], which includes a preliminary study of the ceramics found in the 2021 excavation that was conducted in the area of the wreck of the Mortella II. The material found is of high interest for determining the chronology of the wreck (1527).…”
mentioning
confidence: 99%